Learning Technology on Early Childhood Education: The COVID-19 Pandemic Case - Nurul Fazriah Rifai; Emilly Nzunda, Ibrahim; Kusumawardani, Ratih; Fatimah, Atin (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – This study aims to analyze the learning technology used by early childhood education teachers during the COVID-19 pandemic, this research describes the evaluation of learning technology used by teachers in early childhood education during the COVID-19 pandemic.Design/methods/approach – The research method is quantitative research. Data was collected using a questionnaire method and strengthened by interviews to obtain in-depth data. Questionnaires were distributed to 30 institutions and early childhood education teachers in Serang District, Serang City, Banten Province. Interviews as reinforcing data were conducted using semi-structured interviews. The research sample was obtained through purposive random sampling. Conclusions were drawn from the data analysis process by using quantitative descriptive data analysis techniques.Findings – Learning technology in early childhood education used by teachers of early childhood education institutions in Serang District, Serang City, Banten Province are whatsapp, zoom meeting, and youtube. Teachers can use learning technology for early childhood education optimally. However, the obstacles obtained consist of: signal interference, limited internet data, and limitations of parents assistance or guardians of students in having gadgets.Research implications/limitations – This study has limitations on early childhood education learning in one area of Indonesia. The learning technology used by teachers also focuses on early childhood education. Therefore, higher education levels will have different learning technologies that teachers use.Practical implications – This study implies that learning technology in early childhood education during the COVID-19 pandemic can use whatsapp, zoom meetings, and youtube.Originality/value – This study contributes to the understanding in early childhood education teachers in utilizing learning technology such as whatsapp, zoom meeting, and youtube in carrying out the teaching and learning process during the COVID-19 pandemic. Paper type: Research paper